The Effects of Direct Assessment, Pay-As-You-Earn (PAYE) on Internally Generated Revenue in Ondo State (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study analyzes the effect of personal income tax on internally generated revenue in Ondo State. The specific objectives are to examine the individual contributions of the components of personal income tax on internally generated revenue in Ondo State. This study used both primary sources and secondary sources of data. In doing this, two models were utilized. The secondary data focused on secondary data from eight years record from Ondo State Board of Internal Revenue (OSBIR), while the primary data employed survey through the aid of questionnaires distributed across the three senatorial districts (18 LGAs) of the state. Ordinary Least Square (OLS) regression analysis was adopted to estimate the two models. The findings show that PAYE and other sources of taxes were statistically significant on internally generated revenue in Ondo State in model one. Meanwhile, in model two, the ability of state government to bring in more payers into the tax net and deploy effective collection of PAYE to enhance revenue have positive and statistically significant impact on IGR in the state. It is therefore recommended that the Ondo State government should bring to table the holistic approach to revenue collection of taxes in the state with a view of enhancing internally generated revenue and minimize bureauractic fraud involved on the part of revenue collection officers in the state.